2021
DOI: 10.1002/adem.202100386
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mechanical Properties of GH4169 Alloys by Reversing the Deformation and Aging Sequence

Abstract: Herein, the microstructure evolution and mechanical properties of GH4169 alloys obtained by solution treatment-deformation-two-stage aging (SDA) and solution treatment-two-stage aging-deformation (SAD) are investigated. The results show that the density of average geometrically necessary dislocations and the size of γ" precipitates in the SAD sample are larger than that in the SDA sample. The ultimate tensile strength (UTS) of the SAD sample is 1651 AE 24 MPa, which is 171 MPa higher than that of the SDA sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Qin et al [13] found that when the volume fraction was similar, the strength displayed a rising trend with the increase of γ phase size. A similar phenomenon was reported in the study by Ran et al [14]. They quantitatively calculated the contribution of the precipitated phase to the strength and found that the strength change is sensitive to the size of the γ phase.…”
Section: Introductionsupporting
confidence: 85%
“…Qin et al [13] found that when the volume fraction was similar, the strength displayed a rising trend with the increase of γ phase size. A similar phenomenon was reported in the study by Ran et al [14]. They quantitatively calculated the contribution of the precipitated phase to the strength and found that the strength change is sensitive to the size of the γ phase.…”
Section: Introductionsupporting
confidence: 85%
“…As the modern industry paves the way, many materials are subject to different temperatures in the service environment. [1][2][3] Since their production, nickel-based superalloys have been used mainly in high-temperature environments that can withstand harsh mechanical conditions. [4][5][6][7][8][9] Examples include pressure vessels, nuclear reactors, etc.…”
Section: Introductionmentioning
confidence: 99%